1998
DOI: 10.1094/pdis.1998.82.10.1084
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Races of Colletotrichum lindemuthianum with the Aid of PCR-Based Molecular Markers

Abstract: Inoculation of a common bean differential series is the usual method for identification of races of Colletotrichum lindemuthianum. This procedure is extremely useful for phytopathological as well as breeding purposes, but it requires strict control of the number of spores and incubation conditions. Furthermore, this method may result in misclassifications of isolates because of the subjectivity of symptom evaluation. We propose the use of DNA-based molecular markers as an auxiliary tool to aid the classificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…RAPD markers were used because they have the potential to detect polymorphism in the entire genome as compared to other techniques [23]. RAPD markers have been used for strain differentiation [24], identification and other genetic analysis for several bacterial genera during the last two decades [23,[25][26][27][28]. Taken together, the present study was undertaken to assess the potentiality of RAPD as a marker for analysing the diversity of R. solanacearum collected from some fields of some selected locations.…”
mentioning
confidence: 99%
“…RAPD markers were used because they have the potential to detect polymorphism in the entire genome as compared to other techniques [23]. RAPD markers have been used for strain differentiation [24], identification and other genetic analysis for several bacterial genera during the last two decades [23,[25][26][27][28]. Taken together, the present study was undertaken to assess the potentiality of RAPD as a marker for analysing the diversity of R. solanacearum collected from some fields of some selected locations.…”
mentioning
confidence: 99%
“…In order to determine whether the pattern of infection of the differential cultivars by C. lindemuthianum isolates is a general pattern observed in other studies, a comparison was made of the infection patterns of all races reported in Minas Gerais state in the last 10 years (Fig. 1b; Rava et al., 1994; Vilarinhos et al., 1995; Alzate‐Marin et al., 1997; Mesquita et al., 1998; Sartorato, 2002; Talamini et al., 2002, 2004). These compiled results indicate that the cultivars most frequently found to be susceptible in other studies are Mexico 222, Michelite, MDRK, Perry Marrow, Widusa, Cornell 29242, Widusa and Kaboon.…”
Section: Resultsmentioning
confidence: 99%
“…The genetic diversity of C. lindemuthianum has been investigated using random amplified polymorphic DNA (RAPD) marker analysis (Balardin et al., 1997; Sicard et al., 1997; González et al., 1998; Mesquita et al., 1998; Thomazella et al., 2002; Mahuku and Riascos, 2004), amplified fragment length polymorphism (González et al., 1998) and random amplified microsatellites (RAMs) (Mahuku and Riascos, 2004). These studies have revealed that C. lindemuthianum is a highly variable pathogen that maintains high levels of genetic diversity.…”
Section: Introductionmentioning
confidence: 99%
“…RAPD was used as it has the potential to detect polymorphism in the entire genome as compared to other techniques (Hilton and Penn 1998). RAPD markers have been used for strain differentiation (Mesquita et al 1998), identification and other genetic analysis for several bacterial genera (Akopyanz et al 1992;Mazurier et al 1992;Parent et al 1996;Hilton and Penn 1998;Khoodoo et al 2002).…”
Section: Discussionmentioning
confidence: 99%